THE SPECTRUM THRESHOLD FILTER METHOD FOR CHAFF AND RAIN - Aldrian, Edvin (BPPT, 2002)
Polarization doppler radar observations of chaff and rain were conducted. At least in thevertical pointing case, the spectrum of chaff is much narrower than that of rain. In dataanalysis a new method of filtering chaff data from noise is used. This filter method, named the spectrum threshold filter method, was also applied for rain data for comparison. Instead of using the average power as in the conventional method this fil ter method utilizes the doppler spectral peak power. Consequently this filter method is able to detect a presence of even a single strong doppler velocity signals. Hence the performance of this filter is better with metallic strips, such as chaff, than raindrops. The variation of the filter? s threshold will change significantly the filtered rainfall area but not the chaff one. The filter technique is also useful to detect a narrow but strong spectral data.Pengamatan hujan dan chaff dengan memakai radar dengan polarisasi doppler telahdilakukan. Paling tidak pada posisi tegak lurus, spektrum dari chaff lebih sempit daripada pada butir hujan. Dalam melakukan analisa data kita telah mengembangkan sebuah metoda filtering untuk memilah data chaff dari noise sekitarnya. Metoda filter ini, yang disebut metoda filter spectrum threshold, juga diterapkan pada data hujan sebagai perbandingan. Daripada memakai kekuatan rata-rata dengan metoda umumnya, metoda filter ini memakai puncak spektrum. Sehingga metoda filter ini dapat mendeteksi keberadaan dari hanya sebuah puncak kecepatan doppler dalam sinyal. Pada akhirnya kinerja metoda filter ini lebih baik untuk aplikasi pada pita-pita logam seperti chaff daripada butiran hujan. Variasi dari batas ambang (threshold) dari filter ini akan mengubah area hujan yang terfilter secara drastis tetapi tidak pada data chaff. Teknik filter ini juga berguna untuk mendeteksi spektrum doppler yang sempit tetapi kuat.